Strengthening Teacher Literacy Through Scientific Writing And Best Practice Mentoring In The 3T Region Of Morotai Island - Fahmi Jaguna; Irawati Sabban; Risky Richlos Sarapung; Amrin Sibua; Subhan Hayun; Nurhani Mahmud; Megawati Basri; Ledy Yanti Lessy; Gullyt Karlos Papingka; Zulhasmi Abasa; Dwi Budidarma Sutrisno; Abd Sarman Sibua (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
The limited production of scientific publications by teachers in Indonesia's disadvantaged, frontier, and outermost (3T) regions continues to constrain the development of teacher professionalism and a sustainable literacy culture. This community engagement program was designed to strengthen teachers' capacity to produce scientific papers, document evidence-based best practices, and utilize the Education Report Card as a foundation for school improvement planning. The program was implemented over four months through a collaborative partnership involving the Faculty of Teacher Training and Education, Universitas Pasifik Morotai, Save the Children, and the Stimulant Institute across 13 partner elementary schools in Pulau Morotai. A participatory and collaborative approach was adopted through In-Service Training (IST), On-Service Training (OST), followed by continuous mentoring, monitoring, and evaluation. The program substantially improved teachers' competence in academic writing and reflective teaching practices. Overall, 90% of the scientific manuscripts were completed and submitted to national journals, while 12 of the 13 participating schools successfully produced best-practice reports that satisfied the program standards. The mentoring process also fostered professional learning communities that strengthened collaboration among teachers. These findings indicate that sustained collaborative mentoring provides an effective strategy for cultivating teacher literacy and supporting continuous educational quality improvement in 3T regions.